A clinical study of the rotational alignment of the femoral component in total knee arthroplasty - Ding, Liangjia (J Phys Ther Sci, 2015)
[Purpose] The reasons for femorotibial rotational malalignment after total knee arthroplasty (TKA) were analyzed to provide evidence for clinical knee joint surgery and to reduce complications. [Subjects and Methods] Ninety knees of 60 patients were selected and randomly divided into two groups (n=30). For one group, rotational alignment of the femoral component was determined by the transepicondylar axis and TKA was performed. For the other group, rotational alignment of the femoral component was conducted through 3° external rotation of the posterior femoral condyles. Knee joint specimens were operated with TKA and various biomechanical indices were measured. [Results] The femoral epicondylar axis was a constant, reliable reference for femoral component rotational alignment. When the femoral component was rotated by 0° versus the epicondylar axis, the peak contact pressure on the patellofemoral joint was optimal. When the femoral component was arranged in parallel with Whiteside’s line, the peak contact pressure on the patellofemoral joint varied largely. The patellofemoral contact areas of the two groups were similar. [Conclusion] Axial rotational alignment of the femoral component influenced the contact pressure of patellofemoral joints in TKA more significantly than external rotation of the femoral condyles. It is more reliable to use the femoral epicondylar axis as the reference for the rotational alignment of the femoral component.